Promoting behavioural change to reduce thermal energy demand in households: A review. (March 2019) - Hafner, Rebecca J.; Elmes, David; Read, Daniel
Abstract: A reduction in thermal energy consumption in buildings is vital for achieving the reductions in carbon dioxide (CO2 ) emissions that are part of EU-2050 targets. A key challenge faced by behavioural scientists is to understand what encourages people to adopt more efficient ways of achieving a satisfactory thermal experience. We review the psychological barriers to reducing thermal energy demand in the context of energy-efficient technology adoption, and discuss ways these barriers may be overcome. The barriers include: demand on cognitive resources due to decision complexity; tendency to procrastinate and discount future consequences; deferral to simplifying strategies including repeating past experience and copying the behaviour of others; the desire to act in ways that maintain a positive self-image; and inertia due to fear of regret that one's decision might be 'wrong'. We discuss behavioural approaches to overcome these barriers, such as emphasising public choice of "green" technology, reframing of benefits, simplifying and optimising the choice environment, focusing on symbolic attributes of new technologies, and changing the temporal structure of costs and benefits. We provide a framework of suggestions for future research which together constitute an important first step in informing behaviour change efforts designed to reduce thermal energy consumption in households. Highlights: We review psychological barriers to reducing thermal energy demand in homes. These include action inertia, social norms, temporal discounting, emotion and habit. We discuss each in the specific context of energy efficient technology adoption. Strategies for overcoming the barriers in order to increase uptake are provided. Wider implications for energy demand and future research directions are outlined.